Stereotactic EEG Practices: A Survey of United States Tertiary Referral Epilepsy Centers. Issue 6 (10th September 2022) - Gavvala, Jay; Zafar, Muhammad; Sinha, Saurabh R.; Kalamangalam, Giridhar; Schuele, Stephan
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: Stereotactic EEG (SEEG) is being increasingly used in the intracranial evaluation of refractory epilepsy in the United States. In this study, the authors describe current practice of SEEG among National Association of Epilepsy Centers tertiary referral (level IV) centers. Methods: Using the Survey Monkey platform, a survey was sent to all National Association of Epilepsy Centers level IV center directors. Results: Of 192 centers polled, 104 directors completed the survey (54% response rate). Ninety-two percent currently perform SEEG. Of these, 55% of institutions reported that greater than 75% of their invasive electrode cases used SEEG. Stereotactic EEG was commonly used over subdural electrodes in cases of suspected mesial temporal lobe epilepsy (87%), nonlesional frontal lobe epilepsy (79%), insular epilepsy (100%), and individuals with prior epilepsy surgery (74%). Most centers (72%) used single-lead electrocardiogram monitoring concurrently with SEEG, but less than half used continuous pulse oximetry (47%) and only a few used respiratory belts (3%). Other significant intercenter technical variabilities included electrode nomenclature and choice of reference electrode. Patient care protocols varied among centers in patient-to-nurse ratio and allowed patient activity. Half of all centers had personnel who had prior experience in SEEG (50.5%); 20% of centers had adopted SEEG without any formal training. Conclusions: Stereotactic EEG has become the principal method for intracranial EEG monitoring in the majority of epilepsy surgery centers in the United States. Most report similar indications for use of SEEG, though significant variability exists in the utilization of concurrent cardiopulmonary monitoring as well as several technical and patient care practices. There is significant variability in level of background training in SEEG among practitioners. The study highlights the need for consensus statements and guidelines to benchmark SEEG practice and develop uniform standards in the United States.